2019
DOI: 10.1002/tea.21592
|View full text |Cite
|
Sign up to set email alerts
|

Utility value interventions in a college biology lab: The impact on motivation

Abstract: Science writing, such as lab reports, allows students to form a meaningful understanding of scientific concepts. However, students often view scientific writing as unimportant and utilize surface level approaches when completing writing assignments. The current study implemented three experimental interventions (directly‐communicated, self‐generated, and hybrid) aligned with prior literature and designed to improve the utility value of lab reports in college settings. Participants (n = 1,002) were recruited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…Researchers have also investigated the effects of utility value interventions with college students. In both laboratory and classroom settings, findings from intervention studies supported the idea that utility value interventions could be used to improve students' interest (Durik et al, 2015;Fritea & Opre, 2015;Geerling et al, 2019;Hulleman et al, 2010Hulleman et al, , 2017Kera & Nakaya, 2017;Shechter et al, 2011), perceived utility value of a particular course (Canning & Harackiewicz, 2015;Clinton & Kelly, 2017Curry et al, 2020;Fritea & Opre, 2015;Kosovich et al, 2019;Lindeman et al, 2018;Rosenzweig, Harackiewicz, et al, 2019), and performance (Canning et al, 2018;Canning & Harackiewicz, 2015). Importantly, the intervention appeared to work best for students who needed it the most: students with low expectancies for success, first-generation college students, and students from marginalized groups (Durik et al, 2015;Harackiewicz et al, 2016;Hulleman et al, 2017).…”
Section: Implementation Of the Utility Value Interventionmentioning
confidence: 89%
“…Researchers have also investigated the effects of utility value interventions with college students. In both laboratory and classroom settings, findings from intervention studies supported the idea that utility value interventions could be used to improve students' interest (Durik et al, 2015;Fritea & Opre, 2015;Geerling et al, 2019;Hulleman et al, 2010Hulleman et al, , 2017Kera & Nakaya, 2017;Shechter et al, 2011), perceived utility value of a particular course (Canning & Harackiewicz, 2015;Clinton & Kelly, 2017Curry et al, 2020;Fritea & Opre, 2015;Kosovich et al, 2019;Lindeman et al, 2018;Rosenzweig, Harackiewicz, et al, 2019), and performance (Canning et al, 2018;Canning & Harackiewicz, 2015). Importantly, the intervention appeared to work best for students who needed it the most: students with low expectancies for success, first-generation college students, and students from marginalized groups (Durik et al, 2015;Harackiewicz et al, 2016;Hulleman et al, 2017).…”
Section: Implementation Of the Utility Value Interventionmentioning
confidence: 89%
“…As this study has demonstrated, science texts powerfully convey what kind of work is important within a particular field, which could help change the science culture. Adding value content and prosocial examples to science lectures should also help, but directly communicated connections from instructors are not enough on their own ( Canning and Harackiewicz, 2015 ; Curry et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the evidence in support of using self-generated utility value interventions is more consistent. Self-generated utility value interventions lead to increased perceptions of value (Acee & Weinstein, 2010;Ivanov, 2017;Lindeman et al, 2018), interest (Hulleman et al, 2010 (Canning et al, 2018;Canning & Harackiewicz, 2015;Harackiewicz et al, 2016;Kosovich et al, 2019;Rosenzweig et al, 2020), or a combination of these variables (Canning et al, 2018;Curry et al, 2020;Hulleman et al, 2017;Rosenzweig et al, 2019).…”
Section: Evidence-based Pedagogical Recommendationsmentioning
confidence: 99%